Prometheus up & running : infrastructure and application performance monitoring - Pivotto, Julien; Brazil, Brian (O'Reilly Media, Inc., 2023)
Get up to speed with Prometheus, the metrics-based monitoring system used in production by tens of thousands of organizations. This updated second edition provides site reliability engineers, Kubernetes administrators, and software developers with a hands-on introduction to the most important aspects of Prometheus, including dashboarding and alerting, direct code instrumentation, and metric collection from third-party systems with exporters. Prometheus server maintainer Julien Pivotto and core developer Brian Brazil demonstrate how you can use Prometheus for application and infrastructure monitoring. This book guides you through Prometheus setup, the Node Exporter, and the Alertmanager, and then shows you how to use these tools for application and infrastructure monitoring. You'll understand why this open source system has continued to gain popularity in recent years.
Includes bibliographical references and index
Keywords: Prometheus (Computer file); Computer networks -- Monitoring; Computer networks -- Management; Réseaux d'ordinateurs; Surveillance; Réseaux d'ordinateurs; Gestion; Computer networks; Management; Computer networks; Monitoring